Al-Qurâan Interpretation on Musaâs Story-Related Verses in Surah Al-Kahf, 60-82 - AsÃ¢Â€Â™ad, Mahrus (ASPENSI in Bandung, Indonesia, 2017)
ABSTRACT: Narrative story in Al-Qurâan can be classified into four models, namely: relatively complete narrative model; middle narrative model; brief narrative model; and fragment narrative model. Al-Qurâan contains two per third narrative story of people living in the past. This shows how valuable those narative story in Al-Qurâan since their story serve as an inspiring lesson for Muslim daily life. This Article is aimed at identifying one of the middle narrative story model of Al-Qurâan that is narrative story of Musa found in âsurahâ (chapter) Al-Kahf, verses 60-82. This narrative model only features Musaâs story in âsurah Al-kahfâ and it doesnât fully cover Musaâ story found in Al-Qurâan. Since it presents complete story between Musa and Khidlir, its plot is understandable. Allah ordered Musa to learn from Khidlir, because he thought that he was the smartest man on earth and no one could outperformed him. Allah wanted to teach Musa that in the world, there were many smarter human being than he was, so that he didnât need to be arrogant with the knowledge he possessed. Above the sky there is a higher sky. It was the interaction with Khidlir and learning process that made Musa realized that the knowledge he possessed was not as much as Khidlir possessed. Allah is indeed the source of knowledge. Musa realized that to achieve the best result in learning process, he should not be in the position of ignorance and his teacher was in the state of more knowledgeable. That was what Musa did in his short course, so that he learned successfully from his teacher, Khidlir.KEY WORDS: Education; Al-Qurâan Interpretation; Surah Al-Kahf; Musa and Khidlir; Narrative Story. About the Author: Mahrus Asâad is a Senior Lecturer at the Faculty of Adab and Humanities UIN SGD (State Islamic University, Sunan Gunung Djati) Bandung, Jalan A.H. Nasution No.105 Cipadung, Bandung 40614, West Java, Indonesia. For academic interests, the author is able to be contacted via e-mail at: mahrusasad@uinsgd.ac.idHow to cite this article? Asâad, Mahrus. (2017). âAl-Qurâan Interpretation on Musaâs Story-Related Verses in Surah Al-Kahf, 60-82â in TAWARIKH: International Journal for Historical Studies, Vol.8(2) April, pp.179-188. Bandung, Indonesia: Minda Masagi Press and UIN SGD Bandung, ISSN 2085-0980.Chronicle of the article: Accepted (January 17, 2017); Revised (March 17, 2017); and Published (April 28, 2017).